Smartphones and Programmable Shunts: Are These Indispensable Phones Safe and Smart? - Ozturk, Sait; Cakin, Hakan; Kurtuldu, Huseyin; Kocak, Onur; Erol, Fatih S.; Kaplan, Metin (Elsevier Science Inc, 2017)
OBJECTIVE: This study aimed to determine whether smartphones affect programmable shunts. METHODS: iPhone 5S (Apple Inc., Cupertino, CA, USA) and Samsung Galaxy S5 (Samsung Electronics, Gumi, South Korea) smartphones were chosen for this study. For both phones, magnetic field mapping was performed with 3-dimensional magnetic scanning systems constructed with high-precision motorized stages, and a Hall effect sensor was used to measure the flux density on the smartphone surface. The distance (h) between the distal outlet of the reservoir and the rugby ball of the Strata valve (Medtronic Inc., Minneapolis, MN, USA) was measured using highly sensitive microanalysis optical method. During optical microanalysis, while keeping a 3-cm distance between the valve and the magnetic generator, the h value (mm) was recorded for different magnetic flux densities (MFDs). Then, direct x-ray radiography was performed for radiologic assessment after each process under different magnetic fields. For analysis of the Codman Certas valve (Codman Neuro, Raynham, MA, USA), the magnet orientation and the angle between the magnet with the tantalum ball were measured with the same optical analysis. RESULTS: Maximum MFDs found 62 G for iPhone 5S and 61 G for Samsung Galaxy S5. When the magnetic generator formed a current at 0, 30, 60, and 90 G, the h values of the Strata valve adjusted to 100 mm H2O opening pressure were 320, 280, 190, and 175 mm, respectively. When the magnetic generator was removed from the environment, the h value returned to 320 mm. In direct graphs taken after each optical analysis at different Gauss values, substitution was not observed at the indicator. The angle in the Codman Certas valve was 123.9 degrees, 112.5 degrees, and 103.6 degrees at the magnetic flux densities of 0, 60, and 90 G, respectively. When the magnetic field was removed (0 G), the angle was still 103.6 degrees, suggesting an irreversible effect in the shunt construct. CONCLUSIONS: Smartphones exert reversible effects on Strata programmable valves without producing remarkable radiologic findings and irreversible effects on Codman Certas valves.
Keywords: Hydrocephalus; Magnetic field; Programmable valve; Shunt; Smartphone